2007
DOI: 10.1111/j.1540-8159.2007.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy:

Abstract: CRT induced a gender specific LV remodeling response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…48,49 Similarly, women with defibrillators have fewer hospitalizations and more robust ventricular remodeling than men. [50][51][52] It is unclear why, despite having a biological advantage, women do worse in the population of OHCAs. Factors such as earlier termination of resuscitative efforts, a higher number of rearrests due to more comorbidities, or older age at time of cardiac arrest could be playing a role in women.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Similarly, women with defibrillators have fewer hospitalizations and more robust ventricular remodeling than men. [50][51][52] It is unclear why, despite having a biological advantage, women do worse in the population of OHCAs. Factors such as earlier termination of resuscitative efforts, a higher number of rearrests due to more comorbidities, or older age at time of cardiac arrest could be playing a role in women.…”
Section: Discussionmentioning
confidence: 99%
“…51,52,54 At variance with ICD studies, subgroup analyses of CRT trials suggest that women may have a better response to CRT, although different studies showed conflicting results. [55][56][57] In a post hoc analysis of the Multicenter InSync Randomized Clinical Evaluation (MIRACLE) trial, Woo et al reported significant differences in outcome based on gender, with women randomised to CRT having a significantly lower incidence of the combined endpoint of first heart failure hospitalisation or death compared with women allocated to the placebo arm. On the other hand, no difference was reported among men for the same endpoint.…”
Section: Cardiac Resynchronisation Therapymentioning
confidence: 99%
“…37 In the Registry to Improve the Use of EvidenceBased Heart Failure Therapies in the Outpatient Setting (IMPROVE HF) trial, only 35% of indicated female patients initially had a CRT device, which improved to 65% with increased physician education at 24 months. 38 Arrhythmias in Pregnancy ECG changes in pregnancy include an increase in the resting heart rate by about 10 beats/minute, and a leftward shift of the electrical axis occurring secondary to enlargement of the gravid uterus.…”
Section: Sex Differences In Utilization and Response To Implantable Dmentioning
confidence: 99%